1994
DOI: 10.1080/02652039409374244
|View full text |Cite
|
Sign up to set email alerts
|

Stability of fumonisins (FB1and FB2) in solution

Abstract: The stability of fumonisins B1 and B2 (FB1 and FB2) during 6 week storage was studied in acetonitrile:water (1:1) and methanol at four storage temperatures (-18, 4, 25 and 40 degrees C). Samples were analysed by HPLC with fluorescence detection after derivatization with o-phthaldialdehyde. Decomposition of fumonisins was evident in a methanol solution after 6 week storage at 4, 25 and 40 degrees C (signals for both toxins decreased by 5, 35 and 60%, respectively), whereas no losses were observed in samples sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…Fumonisins B 1 and B 2 standard solutions: Individual stock solutions of FB 1 and FB 2 (Sigma Chemical Company, St. Louis, MO) were prepared dissolving 1 mg in acetonitrile/water (1+1) according to Visconti et al (23). Working solutions were then prepared with concentrations of 50 µg/ml of FB 1 and FB 2 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Fumonisins B 1 and B 2 standard solutions: Individual stock solutions of FB 1 and FB 2 (Sigma Chemical Company, St. Louis, MO) were prepared dissolving 1 mg in acetonitrile/water (1+1) according to Visconti et al (23). Working solutions were then prepared with concentrations of 50 µg/ml of FB 1 and FB 2 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…According to Andrade et al, stock standard solutions of AFLs, ochratoxin A (OTA), zearalenone (ZEA), deoxynivalenol (DON), 3-acetyl-and 15-acetyl deoxynivalenol (3-AcDON and 15-AcDON) and citreoviridin (CTV) were considered valid after a storage period if their UV-spectrophotometric check resulted in a maximum of 3% difference with the previous check of freshly prepared solutions [10]. Some other authors also reported 2%-3% variation as suitable [11,12], while the majority did not address this point. In the present study, the repeatability of intra-day absorbance values was evaluated.…”
Section: Stability Of Diluted Individual Stock Standard Solutionsmentioning
confidence: 99%
“…Traditionally, FBs are monitored by HPLC after their pre-column derivatization with o-phthalic aldehyde [48,49]. This method was used by Visconti et al to monitor methanol and acetonitrile-water (50:50, v/v) FB1 (100 µg/mL) and FB2 (50 µg/mL) standard solutions during storage in fire sealed glass ampoules for six months [12]. Methanol solutions proved to be stable under freezing for six weeks storage, at 4 • C their degradation started in three weeks, about 25% loss was detected within this period at ambient temperature.…”
Section: Fumonisinsmentioning
confidence: 99%
“…This result differs from that of Velázquez et al , who found the best solvent to be methanol. Although methanol was tested as an extraction solvent, FB 1 and FB 2 were not stable enough in methanol , . Therefore water/acetonitrile (1:1 v/v) was used as the optimal solvent for dissolving FB 1 and FB 2 standards and samples.…”
Section: Resultsmentioning
confidence: 99%